SOSIALISASI PENTINGNYA LEGALITAS FORMAL DALAM KEPEMILIKAN TANAH DI GAMPONG PANTON RAYEUK A KECAMATAN BANDA ALAM KABUPATEN ACEH TIMUR - Jumadiah Jumadiah; Jamaluddin J; Muammar M; Sutriani s; Sulaiman S (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Land has an important role in people's lives as infrastructure and resources forgampong communities, especially those in rural areas. Property rights are hereditary,strongest and fullest rights that people can have over land. Whereas regarding theimportance of the formal legality of land ownership it is necessary to provide anunderstanding to the gampong community, and on average the land owned by thesecommunities relies on the Keusyik Decree, according to positive law the legal force is verylow, so it is time for this socialization to be carried out so that the community knows andregister their lands so that they have a strong legal basis, this avoids disputes, so theproblem is how formal legality is in land ownership in Gampong Panton Rayeuk A, BandaAlam District, East Aceh Regency, as well as efforts to increase the knowledge and legalawareness of residents.The purpose of this socialization is for the land to obtain certainty, order and legalprotection for interested parties.The method used is the lecture and discussion method. TheLecture Method is used to provide participants with an understanding of the topic offormal legality service (land registration) related to land ownership. The lecture describedformal legality material related to land ownership in a clear, systematic manner so that itwas easy to understand. While the discussion method is used to provide more opportunitiesfor participants to discuss, question, provide input, and/or deepen the material provided.The output to be achieved is understanding of legal rules/ease for the community inobtaining legality of land